The Position of Humans in Islamic Educational Philosophy - Ghofururrohim, Abdul; Karim, Abdul; Mukaromah, Ning; Romly, Abdul Wahid; Jaenullah, Jaenullah (CV. Bimbingan Belajar Assyfa, 2024)
The concept of human nature and their role in the universe has been a subject of extensive exploration in Islamic philosophy. This article examines how misconceptions about human identity can lead to behaviors of egoism, arrogance, and subjugation. By analyzing Qur'anic verses and the insights of thinkers like Abu al-A'la al-Maududi and 'Abd al-Rahman al-Nahlawi, the paper explores the duality of human potential for greatness and error. The Qur'an provides guidance to transcend arrogance, fostering humility and spiritual growth. This study also delves into the roles of humans as servants of God, khalifah fi alardh (stewards of the earth), and imamrah fi al-ardh (leaders of the earth), emphasizing their responsibility to cultivate a peaceful and prosperous society. The balance between understanding human limitations and leveraging their unique capacities for knowledge is crucial for achieving harmony with the divine and the world.